2017
DOI: 10.1159/000455159
|View full text |Cite
|
Sign up to set email alerts
|

Durham Smith Vest-Over-Pant Technique: Simple Procedure for a Complex Problem (Post-Hypospadias Repair Fistula)

Abstract: Objective: Urethrocutaneous fistula, which occurs after hypospadias surgery, is often a baffling problem and its treatment is challenging. The study aimed to evaluate the results of the simple procedure (Durham Smith vest-over-pant technique) for this complex problem (post-hypospadias repair fistula). Methods: During the period from 2011 to 2015, 20 patients with post-hypospadias repair fistulas underwent Durham Smith repair. Common age group was between 5 and 12 years. Site wise distribution of fistula was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
2
1
0
Order By: Relevance
“…In the present study, complications were de ned as any complaints that required surgical correction, including stula, urethral stricture, and diverticulum. The complication rate of primary operation was 39%, with stula (24 patients, 17.6%) being the most common complication, similar to the previous studies [35]. Both stula and urethral stricture were believed to be related to the poor blood supply to the neourethra and the native urethra[36] Cui et al suggested that surgeons should protect the vascular pedicle of the inner sheath of the foreskin, ensuring the transverse ap is as thick as possible so that the vascular tissue can be preserved.…”
Section: Resultssupporting
confidence: 90%
“…In the present study, complications were de ned as any complaints that required surgical correction, including stula, urethral stricture, and diverticulum. The complication rate of primary operation was 39%, with stula (24 patients, 17.6%) being the most common complication, similar to the previous studies [35]. Both stula and urethral stricture were believed to be related to the poor blood supply to the neourethra and the native urethra[36] Cui et al suggested that surgeons should protect the vascular pedicle of the inner sheath of the foreskin, ensuring the transverse ap is as thick as possible so that the vascular tissue can be preserved.…”
Section: Resultssupporting
confidence: 90%
“…In the present study, complications were defined as any complaints that required surgical correction, including fistula, urethral stricture, and diverticulum. The complication rate of primary operation was 39%, with fistula (24 patients, 17.6%) being the most common complication, similar to the previous studies ( 38 ). Both fistula and urethral stricture were related to the poor blood supply to the neourethra and the native urethra ( 39 ).…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, we usually cover the free graft by rotation of thin subcutaneous tissue, which might explain the relatively high rate of urethrocutaneous fistula in our series. For management of urethrocutaneous fistula, Gite et al [16] reported excellent results of the Durham Smith vest-over-pant technique.…”
Section: Discussionmentioning
confidence: 99%